2016
DOI: 10.1111/jpy.12428
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Saccharina latissima (Phaeophyceae) along a salinity gradient in the North Sea–Baltic Sea transition zone

Abstract: The North Sea-Baltic Sea transition zone constitutes a boundary area for the kelp species Saccharina latissima due to a strong salinity gradient operating in the area. Furthermore, the existence of S. latissima there, along Danish waters, is fairly patchy as hard bottom is scarce. In this study, patterns of genetic diversity of S. latissima populations were evaluated along the salinity gradient area of Danish waters (here designated brackish) and were compared to reference sites (here designated marine) outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 49 publications
(76 reference statements)
2
30
1
Order By: Relevance
“…across broad spatial scales. For example, kelp population comparisons across greater geographic distances in the North and Baltic Seas, as well as in Chinese and Japanese waters, exhibited genetic differentiation an order of magnitude larger (F ST > 0.1) than those observed in the present study (Liu et al 2012; Nielsen et al 2016). Small but significant population structuring, however, was still evident across the small spatial scale in eastern Maine waters, including among individuals in the major embayments of Penobscot, Frenchman, and Cobscook Bays.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…across broad spatial scales. For example, kelp population comparisons across greater geographic distances in the North and Baltic Seas, as well as in Chinese and Japanese waters, exhibited genetic differentiation an order of magnitude larger (F ST > 0.1) than those observed in the present study (Liu et al 2012; Nielsen et al 2016). Small but significant population structuring, however, was still evident across the small spatial scale in eastern Maine waters, including among individuals in the major embayments of Penobscot, Frenchman, and Cobscook Bays.…”
Section: Discussioncontrasting
confidence: 75%
“…In addition, two loci used in the present study were monomorphic across populations. Using the same markers, most individual kelp populations in European waters exhibited larger allelic richness and heterozygosity, irrespective of geographic location (Nielsen et al 2016; Paulino et al 2016). The only previously sampled European population, at these markers, to exhibit somewhat similar heterozygosities to those in the present study was found in the more isolated Vejle Fjord in Denmark (H o = 0.318, H e = 0.358), which was within the North Sea-Baltic salinity transition zone and characterized by a small population size and limited connectivity (Nielsen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations